Atopy Increases Risk of Psychotic Experiences: A Large Population-Based Study - Begemann, Marieke J.H.; Linszen, Mascha M.J.; de Boer, Janna N.; Hovenga, Wytske D.; Gangadin, Shiral S.; Schutte, Maya J.L.; Sommer, Iris E.C. (Frontiers in Psychiatry, 2019)
Introduction: Building upon the comorbidity between atopy and schizophrenia, we conducted a large cross-sectional, observational population-based study to examine if such associations also exist between atopic disorders (eczema, allergic rhinitis, and asthma) and nonclinical psychotic experiences. Methods: We examined psychotic experiences in a Dutch population sample through an online survey (≥14 years of age). Participants filled out the Questionnaire for Psychotic Experiences, together with questions screening for atopic disorders (eczema, allergic rhinitis, and asthma). Prevalence rates were calculated; binary logistic regression was used to determine odds ratios (ORs) (age, gender, and years of education as covariates). Results: We included 6,479 participants. Individuals diagnosed with one or more atopic disorders had an increased risk of psychotic experiences as compared with controls (OR = 1.26). Analysis of individual symptoms revealed an OR of 1.27 for hallucinations, whereas delusions only showed a trend. With each additional atopic disorder, the risk of psychotic experiences increased. This was also observed for hallucinations alone but not for delusions alone. Atopy was associated with hallucinations across all modalities (OR ranging from 1.19 to 1.40). These results did not appear to be driven specifically by any one of the atopic disorders. Conclusion: In the largest population sample of adolescents and adults to date, we found that atopic disorders (asthma, eczema, and allergic rhinitis) increase the risk of psychotic experiences, in a dose–response fashion. These results provide further support for the role of immunological components in the predisposition for psychosis and can serve as a base for further research.